Origins of Epilepsy in Fragile X Syndrome - Hagerman, Paul J (Blackwell Science Inc, 2009)
Fragile X syndrome is the leading heritable form of cognitive impairment and the leading known monogenic disorder associated with autism. Roughly one-quarter of children with this disorder have seizures, most of which are relatively benign and are resolved beyond childhood. Because of the prevalence of fragile X syndrome, numerous animal models have been developed and electrophysiological studies have taken place to investigate its pathogenesis. The investigations have yielded a wealth of information regarding the synaptic dysfunction that underlies the hyperexcitability and epileptiform features associated with this disorder.